2022
DOI: 10.1029/2021wr029576
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nonlinear Time Series and Machine Learning Algorithms for Forecasting Groundwater Flooding in a Lowland Karst Area

Abstract: In karst limestone areas interactions between ground and surface waters can be frequent, particularly in low lying areas, linked to the unique hydrogeological dynamics of that bedrock aquifer. In extreme hydrological conditions, however, this can lead to wide‐spread, long‐duration flooding, resulting in significant cost and disruption. This study develops and compares a nonlinear time‐series analysis based nonlinear autoregressive model with exogenous variables (NARX), machine learning based near support vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Groundwater studies using AI and GRACE data have been carried out for some years (Gemitzi & Lakshmi, 2017; Sun, 2013; Sun et al., 2019). Wave decomposition methods are also very useful in hydrological studies for flow prediction, seasonal analysis or even hydrogeological studies (Ashraf et al., 2022; Basu et al., 2022; Erkyihun et al., 2016; Qi & Neupauer, 2008). Hybrid use of AI and wavelet decomposition techniques turned out to be an important and active research area, resulting in more accurate models in water resources applications, due to its great ability to discriminate non‐stationary and nonlinear trends that occur at different scales in groundwater time series (e.g., Tao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater studies using AI and GRACE data have been carried out for some years (Gemitzi & Lakshmi, 2017; Sun, 2013; Sun et al., 2019). Wave decomposition methods are also very useful in hydrological studies for flow prediction, seasonal analysis or even hydrogeological studies (Ashraf et al., 2022; Basu et al., 2022; Erkyihun et al., 2016; Qi & Neupauer, 2008). Hybrid use of AI and wavelet decomposition techniques turned out to be an important and active research area, resulting in more accurate models in water resources applications, due to its great ability to discriminate non‐stationary and nonlinear trends that occur at different scales in groundwater time series (e.g., Tao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The ARX model is widely used to model a number of engineering optimization problems such as electrical/power systems [35], estimating battery charge [36], predicting electrical loads [37] and forecasting gas emissions and water flooding [38][39][40]. The parameter estimation of the ARX model is of paramount significance owing to its ability to model different phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Shiri et al [9] proposed an extreme learning machine (ELM) approach to predict daily water levels of Urmia Lake in Iran, and outcomes of the ELM model were compared with those of genetic programming (GP) and artificial neural networks (ANNs). Basu et al [10] developed and compared a nonlinear time-series analysis-based nonlinear autoregressive model with exogenous variables (NARX), machine learning-based near-support vector regression, as well as a linear time-series ARX model in terms of their performance to predict groundwater flooding in a lowland karst area of Ireland, and the results indicated that the performances of all of the models were all similarly accurate up to 1-10 days into the future. Kim et al [11] used three machine learning models, gradient boosting (GB), support vector model (SVM), and long short-term memory (LSTM), for real-time flood forecasting of Namhan river in Korea, by comparing with storage function model (SFM), and the results showed that LSTM model had the best predictive power.…”
Section: Introductionmentioning
confidence: 99%